BREAST CANCER IN MEN: AN EPIDEMIOLOGICAL OVERVIEW OF THE DISEASE IN THE CENTRAL-WEST REGION OF BRAZIL OVER THE LAST 40 YEARS - Cunha, Luisa Veras Cordeiro da; Silva, Ana Gabriela Brandão; Rodrigues, Leandro Nascimento da Silva (CIPEEX, 2025)
Advances in medicine and science have brought advanced care techniques, but significant challenges remain, especially in relation to rare diseases such as male breast cancer. This neoplasm is rarely discussed and often underserved due to its much lower prevalence in men compared to women. In this context, the objective of the present study is to identify the risk factors for the development of male breast cancer and describe the therapeutic measures for its resolution. The work is configured as an analytical, quantitative, descriptive, retrospective study, which was carried out based on data collected from platforms, in addition to the use of data and information collected from the Notifiable Diseases Information System (SINAN) of DATASUS. The analysis of the studies and data reveals that the main risk factors for male breast cancer include advanced age at diagnosis, genetic factors such as mutations in the BRCA1 and BRCA2 genes, Klinefelter syndrome, positive family history, hormonal changes, occupational exposures, diet, and alcohol consumption. The standard treatment is mastectomy combined with endocrine therapy. In addition to surgical treatment, radiotherapy, chemotherapy, and some medications may also be included in the treatment plan. Finally, there is still a complexity in fully understanding breast cancer, so awareness and advances in understanding the disease are essential to address the challenges associated with this rare condition.